Katekese Sekolah Menengah Mengenai Yesus Sebagai Sahabat Sejati dan Tokoh Idola Pada Peserta Didik Kelas XA SMAK Frateran Malang - Agnes Ranubaya, Fransesco; Meo, Yohanes Wilson B. Lena; Handoko, Petrus Maria (Vocat : Jurnal Pendidikan Katolik, 2023)
Young people often idolize models or idols regarding their lifestyle and charm. It would be wonderful if that fascination was directed towards Jesus Christ, the Savior. Admiration for these individuals is often driven by their exceptional values, traits, character, abilities or appearance, which embody the aspirations and aspirations of the admirer. This admiration can also lead to a longing for a relationship with the idolized figure, either directly or indirectly. The research methodology used is a qualitative method. The data used in this research was collected from news sources, books, and journals. The findings in this study conclude that what is formulated as the main problem is answered that catechesis on "Jesus as a true friend and idol figure" can affect the depth of faith and real action in the lives of students. This finding is also a very meaningful input for Catholic Religious Education teachers who become catechesis facilitators in schools to be more proactive and skillful in delivering teaching materials.